Language use on twitter among Malaysian L2 speakers / Noor Aqsa Nabila bt Mat Isa - Mat Isa, Noor Aqsa Nabila (2014)
Twitter, being a mode of computer-mediated communication (CMC), has portrayed an interesting language use in the medium given that it has a 140 character limitation. In this study, the impact of this limitation on language use has been investigated with distinctive attention to its linguistic features as well as the shortening strategies employed by Malaysian Twitter users. Two frameworks were used to analyse the features and the strategies; (1) the linguistic features of short texts (Ling and Baron, 2007) and (2) shortening strategies (Dabrowska, 2011). The author presents the findings by means of qualitative and quantitative analysis that show the frequency of linguistic features categorized into three areas; (1) emoticons and lexical shortenings, (2) sentence punctuation and (3) length. Shortening strategies include occurrences of clipping and contractions, deletion of vowels, non-standard spelling, word-letter substitutions, deletion of apostrophe and also deletion of pronouns and auxiliaries. The perceptions given by the participants on the language use in Twitter specifically on the creativity and clarity of tweets within the limited space are also analysed. The results show that the frequencies calculated for the features and strategies were relatively small on the whole; however, they have revealed gender differences in the language use. Furthermore, the present study confirms that language is neither deteriorating nor are users less efficient to convey their message clearly and successfully. It is hoped that this study will provide a better understanding of the phenomenon of language use on Twitter by Malaysian users. Keywords: computer-mediated communication, Twitter, character limitation, linguistic features, shortening strategies, gender differences, perceptions